NOx Formation of Co-combustion of Sweet Sorghum Lignite (Orhaneli) Mixtures in Fluidised Beds - Cubuk, M. Handan; Ozkan, Derya B.; Emanet, Oztem (SPRINGER-VERLAG BERLIN, 2011)
Nitric oxide is an acid rain precursor and participates in the generation of photochemical smog through ozone production. In addition, nitrous oxide is a greenhouse gas. Thus, the reduction of emissions of nitrogen oxides is currently a major environmental issue. In this study, Sweet sorghum was chosen as the energy plant. Combustion experiments of lignite and lignite-sweet sorghum mixtures were carried out in a fluidized bed system. The fuel-feeding ratio was set such that the thermal output of the system remained constant. Addition of Sweet sorghum to the lignite reduces the pollutant concentration. The results were supported by experimental results.
Keywords: Sweet sorghum; Co-combustion; Fluidized bed; Nitrous oxide; COAL COMBUSTION; N2O EMISSIONS; ENERGY; Environmental Sciences & Ecology